KOMPARATIF EFISIENSI PERBANKAN SYARIAH DAN PERBANKAN KONVENSIONAL DI INDONESIA - Rosyadi, Imron; Fauzan, Fauzan (Benefit: Jurnal Manajemen dan Bisnis, 2011)
The purpose of this study was to: (i) acknowledge and examine the differences between the financial performance of Islamic banking with conventional banking, (ii) to analyze and explain the differences in efficiency levels between Islamic banking and conventional banking (iii) analyze and compare the efficiency of Islamic banking with banks conventional. The population used in this study is a commercial bank in Indonesia with 124 banking institutions with the details of five state banks and 119 private banks. sample of banking institutions in this study are 5 government-owned banking institution (s) and 3 institutions of Islamic banks. The method of analysis used in quantitative research is descriptive (analytic). Measurement and test efficiency and efficiency ratio of the difference of Islamic banking from conventional banking to use Supplier Data Analysis (DEA) and two different test mean (t-test). The results showed during the observation period 2006-2010, economic activities (banking) of Islamic banks are relatively more efficient than conventional banks